2018
DOI: 10.1556/2060.105.2018.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iloprost on contractile impairment and mitochondrial degeneration in ischemia-reperfusion of skeletal muscle

Abstract: Purpose Acute lower extremity ischemia is still a main cause of mortality and morbidity in orthopedic traumatology and reconstructive surgery. In acute lower extremity ischemia, the skeletal muscles are the tissues that are the most vulnerable to ischemia. The aim of this study was to evaluate the effects of iloprost (IL) therapy on skeletal muscle contractile impairment and mitochondrial degeneration in an acute lower extremity ischemia-reperfusion rat model. Main Methods Forty Wistar albino rats were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Similar to BRL, the antioxidant potential of BRL is known to decrease when these receptors are inhibited [2]. The benefit of ILO administration in preventing the skeletal muscle damage following IR has been demonstrated [3]. In addition, it has been reported that the level of antioxidant enzymes increases during IR damage in rats treated with ILO [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to BRL, the antioxidant potential of BRL is known to decrease when these receptors are inhibited [2]. The benefit of ILO administration in preventing the skeletal muscle damage following IR has been demonstrated [3]. In addition, it has been reported that the level of antioxidant enzymes increases during IR damage in rats treated with ILO [4].…”
Section: Discussionmentioning
confidence: 99%
“…Iloprost (ILO) is a PGI2 (prostacyclin) analog [3]. ILO has effects such as inhibition of platelet aggregation, arteriovenous dilatation, increased capillary permeability due to the release of mediators (e.g., serotonin and histamine), increased endogenous fibrinolytic activity, and anti-inflammatory effects (such as inhibition of leukocyte adhesion after endothelial damage and reduced TNF (tumor necrosis factor) alpha release [3,4]. BRL 37344 (ß3 adrenergic receptor activation) is a selective ß3receptor agonist (ß3-RA).…”
Section: Introductionmentioning
confidence: 99%
“…18 studies used rats in their experimental design. Of these 18 studies, nine articles used Sprague-Dawley rats [23][24][25][26][27][28][29][30][31], one used Wistar albino rats [32], seven studies used Lewis rats [33][34][35][36][37][38][39], and one study used Fisher rats [40]. Five of the 29 articles used mice in their experimental design.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Ischemia and I/R models were used for all the included studies (Table 1). These studies used either elastic non-pneumatic tourniquet [26,27,29,32,40,49], pneumatic tourniquet [23,31,33,34,[41][42][43], atraumatic clamps [24,25,28,[46][47][48]51], or ligation methods [30,39,44,45] to produce ischemia in the hind limbs. Specifically, four of the studies amputated the thigh sparing femoral vessels, later femoral vessels were occluded to avoid venous congestion and create ischemia [35][36][37][38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This paper was published as part of the "Translational Geroscience" initiative of Physiology International [51][52][53][54][55][56][57][58][59][60][61].…”
Section: Acknowledgmentmentioning
confidence: 99%